E-Learning Readiness and Job Stressor of Elementary School Teachers in the Covid-19 Pandemic - Dwianasari, Riani; Kekalih, Aria; Fitriani, Dewi Yunia; Soemarko, Dewi Sumaryani; Fuadi, Ahmad (Proceedings Book of International Conference and Exhibition on The Indonesian Medical Education Research Institute, 2022)
Background: E-learning readiness became a new workload for teachers during the Covid-19 pandemic because of the obligatory online teaching. E-learning readiness comprises four factors: the readiness of technology, innovation, people, and self-development; and it might cause job stressors and affect teachers' performance. The research objective was to explore job stressors that influence teachers the most and how they might be associated with E-learning readiness. Method: The cross-sectional method assessed 186 teachers from public and private elementary schools in the urban city area in Jakarta. The data obtained from questionnaires: Teacher Stress Inventory (TSI) Boyle and E-learning Readiness (ELR) Aydin and Tasci. TSI assessed teachers' job stressors in five main components: workload, student behavior, professional recognition, time and resources, and interpersonal relationships. Results: Most teachers perceived readiness at e-learning (84.9%). E-learning readiness was a profound problem for female and non-classroom teachers. The dominant job stressors for teachers were workload (27%), professional recognition (22%), time and resources (21%), and student behavior (21%). The number of students influenced workload and professional recognition. Self-development was the prominent e-learning readiness factor associated with teacher job stressors, especially professional recognition. Conclusions: In urban areas like Jakarta, fifteen percent of teachers remain unprepared for e-learning teaching. The unpreparedness was related to the female gender and non-classroom teachers, who need e-learning skills training to improve their readiness and control job stressors for better teaching performance in a prolonged pandemic situation.